The stratigraphy and sedimentology of the Upper Johannesburg and Turffontein Subgroups in the Southwestern portion of the Welkom Goldfield - Bailey, Andrew Charles (My University, 2016)
This study documents and interprets the stratigraphy and sedimentary environments of the upper Johannesburg and Turffontein Subgroups of the Witwatersrand Supergroup on St. Helena Gold Mine. These data are used to construct a tectono-stratigraphic framework and determine the general distribution of economic mineralization. [Abbreviated abstract. Open document to view full version]
Thesis (M.Sc.)--University of the Witwatersrand, Faculty of Science, 1991
Keywords: Geology, Structural--Research--South Africa--Free State